HUBUNGAN ANTARA FAKTOR KARAKTERISTIK DEMOGRAFIK DENGAN KEPATUHAN GAYA HIDUP SEHAT PADA PASIEN HIPERTENSI - Emi Eliya Astutik; Irwina Angelia Silvanasari; Roby Aji Permana (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2024)
Background: Hypertension is not only found in the elderly group, but now the incidence rate is also increasing in the productive age group. The increase in the incidence of hypertension occurs due to a lack of healthy lifestyle behavior Purpose: The aim of this study is to analyze the relationship between demographic characteristic factor with healthy lifestyle compliance in hypertension patient Methods: This research is a correlation study with a sample of 150 hypertension sufferers. Independent variables, namely demographic characteristic factors, include age, education, knowledge and duration of illness. The dependent variable is adherence to a healthy lifestyle. Data were collected using a questionnaire on demographic characteristic factors and healthy lifestyle adherence. Data analysis used the gamma correlation test Result: The research results showed that there was no relationship between age and adherence to a healthy lifestyle (p value=0.150 > 0.05). There is a relationship between education and adherence to a healthy lifestyle (p value = 0.041 < 0.05). There is a relationship between knowledge and adherence to a healthy lifestyle (p value = 0.043 < 0.05). There is no relationship between disease duration and adherence to a healthy lifestyle (p value = 0.153 > 0.05) Implication: Good education and knowledge can keep hypertensive patients away from non-compliance with a healthy lifestyle, although there are still hypertensive patients who are not fully compliant in living a healthy lifestyle. Health workers can maximize adherence to a healthy lifestyle for hypertension sufferers by providing health education related to their hypertension.